Protecting satellite systems from disassociation DoS attacks - Ma, Ting (2013)
With the help of satellites, the entire surface of the world can be covered, which provides the high speedy communications all over the world. Consequently, security is becoming an important concern in the satellite multicast communications. However, due to the inherent dynamic broadcast nature of the communication medium, this multicast system is easily susceptible to interferences and interceptions. In addition, the satellite system generally has a large number of terminal members with the high frequent join-leave characteristic. Therefore, the satellite systems face significant security challenges. The denial of service (DoS) is one of the most harmful attacks to the satellite systems and also terrestrial fixed or mobile networks. It can maliciously prevent legitimate users from accessing the service. It is especially true for the disassociation DoS attacks where an attacker sends bogus disassociation requests to disable the communication between the server and their legitimate clients. In this paper, the main focus of our work is to detect and defend against the disassociation DoS attacks on the satellite system. We also provide preliminary modeling verifications and simulation results regarding the efficiency and practicability of this new approach. Further analysis of the proposed method is also appended to demonstrate its feasibility.